Creating an earthquake scenario in China: A case study in Weinan City, Shaanxi province. (January 2020) - Rodgers, Janise; Su, Guiwu; Qi, Wenhua; Milledge, David; Densmore, Alexander; Davis, Craig; England, Philip; Young, John; Cao, Yue; Chakos, Arrietta; Li, Xiaoli; Sim, Timothy; et al.
Abstract: In efforts to address government-identified gaps between top-down policies and local-level preparedness approaches, a team from China, the UK and the US undertook a transdisciplinary, participatory project to develop an earthquake scenario for two administrative districts of Weinan, Shaanxi province, located east of Xi'an. We designed the scenario study and communication materials, a first of their kind in China, to help local agencies describe and communicate earthquake risk to local decision-makers and the public. Weinan was destroyed by the 1556 M8¼ Huaxian earthquake, China's deadliest so far, and damaged by the 1568 M 7 Shaanxi Gaoling earthquake (also known as the M6¾ Northeast Xi'an earthquake). We chose a repeat of this 1568 event, because earthquakes of the size of the 1556 Huaxian event are extremely rare in the Weihe basin (and similar tectonic environments worldwide). We modelled the ground motion of the 1568 event, prepared a loss estimate, conducted field charrettes comprising field work and local consultations, and carried out disaster issue-focused social surveys to understand Weinan's main earthquake risk problems. We used a storytelling approach to create two science-based narratives, in Chinese and English, of the scenario earthquake's aftermath. One is a short graphic novel with earthquake mitigation and preparedness tips for the general public; the other is a narrative story with technical content and recommendations for relevant local agencies. The narratives can help people visualize the estimated losses and impacts, and provide mitigation and preparedness recommendations that, if implemented, will help reduce earthquake damage and consequences.